2023
DOI: 10.1097/fm9.0000000000000179
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Transmission of Severe Acute Respiratory Syndrome Coronavirus 2: Current Evidence and Perspectives

Abstract: Evidence of SARS-CoV-2 intrauterine vertical transmissionSince the onset of the pandemic, worldwide efforts were made to explore the possibility of vertical transmission of SARS-CoV-2. The first study from China reported a retrospective cohort of nine pregnant women with SARS-CoV-2 infection, by RT-PCR analyses of the virus, on babies born to mothers with SARS-CoV-2 infection and their paired amniotic fluid and cord blood. The study indicated no evidence of intrauterine vertical transmission in late pregnancy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…[16] Evidence indicated that in utero transmission of SARS-CoV-2 is possible based on the detection of SARS-CoV-2 in intrauterine tissue samples, such as amniotic fluid, placenta, and umbilical cord plasma. [17] Besides, placental expression of ACE2 and transmembrane protease serine 2 (TMPRSS2) required for SARS-CoV-2 entering the cells makes the transplacental transmission of SARS-CoV-2 theoretically feasible. [17] However, the rates of intrauterine vertical transmission of SARS-CoV-2 seem to be uncommon.…”
Section: Maternal and Fetal Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…[16] Evidence indicated that in utero transmission of SARS-CoV-2 is possible based on the detection of SARS-CoV-2 in intrauterine tissue samples, such as amniotic fluid, placenta, and umbilical cord plasma. [17] Besides, placental expression of ACE2 and transmembrane protease serine 2 (TMPRSS2) required for SARS-CoV-2 entering the cells makes the transplacental transmission of SARS-CoV-2 theoretically feasible. [17] However, the rates of intrauterine vertical transmission of SARS-CoV-2 seem to be uncommon.…”
Section: Maternal and Fetal Outcomesmentioning
confidence: 99%
“…[17] However, the rates of intrauterine vertical transmission of SARS-CoV-2 seem to be uncommon. [17] Additionally, the data on the safety of breastfeeding among mothers infected with SARS-CoV-2 are reassuring. [17] To date, the long-term health consequences of maternal SARS-CoV-2 infection for both the mother and offspring remain largely unclear.…”
Section: Maternal and Fetal Outcomesmentioning
confidence: 99%
See 3 more Smart Citations